PENGARUH STIMULASI KUTANEUS SLOW STROKE BACK MASSAGE (SSBM) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Oktovina Mobalen; Dian Veronica Werung; Yehud Maryen (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2020)
EFFECT OF KUTANEUS SLOW STROKE BACK MASSAGE (SSBM) STIMULATION ON BLOOD PRESSURE REDUCTION IN HYPERTENSION PATIENTS Oktovina Mobalen1, Dian Veronica Werung2 Yehud Maryen3 1 Lecturer staff of Poltekkes Kemenkes Sorong 2Students of the Nursing Department of the Health Polytechnic of the Ministry of Health, Sorong 3 Lecturers of Poltekkes Kemenkes Sorong email: mimaopin@gmail.com ABSTRACT Background: Hypertension is defined as an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements. Objective: To determine the effect of Cutaneous Slow Stroke Back Massage (SSBM) stimulation on blood pressure reduction in hypertensive patients at the Majar Puskesmas, Salawati District, Sorong Regency. Research Methods: This study uses quantitative research using a quasi-experimental design and a pretest posttest approach. The research population is all hypertension sufferers every month of 2017 as many as 43 respondents with total population techniques. Materials and data collection tools used in this research are phygmomanometer, stethoscope and sheets Observation. Univariate data analysis to describe the characteristics of respondents and bivariate analysis used T test with Dependent T-Test. Results: The results of statistical tests using the T Dependent T-Test obtained p value = 0.043 on the effect of Cutaneous Slow Stroke Back Massage (SSBM) stimulation on lowering blood pressure in hypertensive patients. Conclusion: there is an effect of Cutaneous Slow Stroke Back Massage (SSBM) stimulation on blood pressure reduction in hypertensive patients Keywords: Cutaneous Stimulation Slow Stroke Back Massage (SSBM), Lowering Blood Pressure, Hypertension